Computational Modeling of Nanoindentation on Emerging Materials: Auxetics, Hard Thin Films and Cohesive-Frictional Solids - Photiou, Demetris (Department of Mechanical Engineering and Material Science and Engineering, Faculty of Engineering and Technology, Cyprus University of Technology, 2019)
Nanoindentation has evolved into a ubiquitous tool for the mechanical characterization of materials at small scales. Several mechanical metrics are routinely extracted, the most common of which are the elastic modulus and the hardness of the indented material. Perhaps, even more importantly than the capability for nanoscale mechanical characterization, is the fact that it provided experimentalists with an unprecedented access to fundamental material physics. This enabled a refined understanding of the underlying mechanisms that yield the macroscopic mechanical response of materials and enabled materials scientists and engineers in developing models and routes for tailor-made synthesis of materials for specific applications. This capability, however, triggered the uncontrolled utilization of nanoindentation in virtually all material systems: metals, ceramics, polymers, composites, biomaterials, thin films, etc. The initial framework of data analysis, however, was developed for metals and it is not necessarily suitable for other materials systems. The utilization of nanoindentation into more complex systems requires the incorporation of the peculiarities of the constitutive relations of the material characteristics and geometrical details into the analysis. This thesis deals with the computational (finite element) modeling of nanoindentation on a variety of emerging materials systems. The three material types studied herein are: (a) auxetic, (b) hard thin films, and (c) cohesive-frictional solids. Auxetics are materials that possess a negative Poisson’s ratio and exhibit the counter-intuitive response of expanding laterally when stretched. This intriguing response provides auxetic systems several augmented characteristics among of which is an enhancement in indentation resistance. Hard thin films are nowadays widely used as protective coatings from mechanical/contact loads or corrosive environments or for additional functionalities like sensing capabilities or biocompatibility. Cohesive-frictional materials are solids with a pressure-sensitive yield criterion. Several important materials fall within this category among them cement-based composites (the most widely used solids on earth), shales (the material in which the majority of hydrocarbon resources is stored) and bulk metallic glasses (one of the most promising advanced metals with enhanced strength and ductility characteristics). The focus of this thesis is twofold: On one hand it aims in deciphering the underlying physics of these materials systems when indented by rigid probes and on the other hand to develop the necessary framework for experimentalists to properly interpret the obtained data, plan their experimental protocol accordingly or develop strategies for material optimization.
Keywords: Nanoindentation; Contact mechanics; Finite element method; Auxetics; Thin films; Cohesive-frictional materials; Νανοδιείσδυση; Μηχανική επαφών; Μέθοδος πεπερασμένων στοιχείων; Αυξητικά υλικά; Λεπτά υμένια; Υλικά με συνοχή και εσωτερική τριβή